Calcium aluminate cement aqueous suspensions as binders for Al2O3-based particle stabilised foams. Issue 6 (15th March 2021) - Santos, T.; Machado, V.V.S.; Borges, O.H.; Salvini, V.R.; Parr, C.; Pandolfelli, V.C.
Abstract: Macroporous refractory ceramics were prepared with Al2 O3 -based particle stabilised foams in which ceramic particles were partially hydrophobized with propionic acid or l -leucine. Calcium aluminate cement (CAC) as dry powder or stable aqueous suspension were added as binders. Cement addition resulted in solid foams whereby setting took place in less than 24 h. Highly porous samples were attained with leucine-based foams whereas the propionic-acid ones were not stable after CAC addition. For leucine-based foams, fired samples with homogeneous microstructures, both high porosity ( 80%) and cold crushing strength ( 30 MPa) were attained when CAC aqueous suspension was used instead of CAC dry powder. These results were associated to the better dispersion of cement particles in the foam structure when CAC liquid binder was used and pointed out the advantages of this suspension for producing solid macroporous ceramics based on particle-stabilised foams.